Peningkatan Akuntabilitas Pengelolaan Dana Desa Melalui Pelatihan di Desa Oelami Kecamatan Bikomi Selatan Kabupaten Timor Tengah Utara - Handrianus Vianey Melin Wula; Elpius Kalembang; Fransiskus Atok; Fetronela Rambu Bobu (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2026)
Proper management of Village Funds plays a crucial role in improving development outcomes and community welfare at the village level. Although the Indonesian government has allocated Village Funds to strengthen rural development, many villages continue to face various challenges in managing these resources effectively. The community service program carried out in Oelami Village, Bikomi Selatan Subdistrict, North Central Timor Regency, was designed to enhance the capacity of village officials in managing Village Funds more efficiently. Using the Participatory Learning and Action (PLA) approach, participants received guidance on village financial planning, implementation, and reporting, with a strong emphasis on transparency and accountability. The training resulted in improved understanding among village officials in preparing the APBDes, monitoring program implementation, and drafting accountability reports. Participants also demonstrated strong engagement and began to recognize that accountable financial management is not only about complying with regulations but also about building public trust and accelerating development in the village.